Offshoring usług informatycznych - Sobińska, Małgorzata (Information technology offshoring, 2006)
The article describes one of the types of information technology outsourcing – offshore outsourcing. The aim of the article is to present the motives, risks and knowledge transfer in offshoring. The challenges of outsourcing become especially acute when the work is being done in a different country (offshored), since that involves language, cultural and time zone differences.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1134, s. 65-70